Analisis Pengaruh Kepemimpinan Transformasional dan Transaksional terhadap Perilaku Kerja Inovatif dengan Komitmen Organisasi sebagai Variabel Mediasi - Sri Haryanto (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
This study addresses the growing challenge of declining innovative work behavior among employees amid the emerging phenomenon of job hugging, where individuals remain in their positions despite limited satisfaction and development opportunities. The primary objective of this research is to examine the effects of transformational and transactional leadership on innovative work behavior, with organizational commitment serving as a mediating variable. A quantitative explanatory approach was employed using survey data collected from 500 formal-sector employees working in private companies in Jakarta. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3 to assess the measurement and structural models, including validity, reliability, and hypothesis testing. The results indicate that transformational leadership has a strong and positive effect on innovative work behavior, both directly and indirectly through organizational commitment. Transactional leadership also shows a positive but relatively weaker influence, primarily through structured reward mechanisms. Furthermore, organizational commitment significantly mediates the relationship between leadership styles and innovative work behavior. These findings highlight the critical role of effective leadership in fostering employee commitment and sustaining innovation, particularly in organizational environments characterized by high retention but limited mobility.